2014
DOI: 10.1353/hsj.2014.0000
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Academic Engagement and Success of Black Male Student-Athletes

Abstract: The goal of this study was to provide a qualitative look at the factors associated with the academic engagement and success of Black male student-athletes in high school. The research team employed a thematic analysis to examine semi-structured interviews conducted with two successful Black male student-athletes, along with their principal, teachers, parents, and coaches. The results suggest that a consistent, collaborative approach laden with cultural competence is necessary to facilitate such outcomes. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Some students enjoy spending unstructured lunch and recess time, and others fret these experiences. Some students feel connected due to their experiences participating in extracurricular activities (Harris et al, 2014; Storlie et al, 2019) while others do not feel comfortable, nor do they desire to get involved (Minor & Benner, 2018). To this end, IBPA assists school counselors with identifying culturally insensitive gaps in activities, perceptions about the climate of safety for multiple marginalized communities, and exclusionary policies resulting in invisibility and marginalization for students.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Some students enjoy spending unstructured lunch and recess time, and others fret these experiences. Some students feel connected due to their experiences participating in extracurricular activities (Harris et al, 2014; Storlie et al, 2019) while others do not feel comfortable, nor do they desire to get involved (Minor & Benner, 2018). To this end, IBPA assists school counselors with identifying culturally insensitive gaps in activities, perceptions about the climate of safety for multiple marginalized communities, and exclusionary policies resulting in invisibility and marginalization for students.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…For the present study, active academic engagement is defined as the self-report of often speaking up in classasking questions, answering questions, and making comments (Harris, Hines, Kelly, Williams, & Bagley, 2014;Reason, Terenzini, & Domingo, 2006). Several putative correlates are explored in each of two waves of data collection, with the second wave treated as an internal replication.…”
Section: Introductionmentioning
confidence: 99%
“…There is a plethora of studies concerning specific middle school achievement and reasons for under-achievement, including studies of students with special education diagnoses, gifted and talented status, or athletic ability (Ford, Grantham, & Whiting, 2008;Good, Masewicz, & Vogel, 2010;Harris, Hines, Kelly, Williams, & Bagley, 2014;. Likewise, research on middle school achievement is readily found in relation to parent, peer, and community influences and school outcomes (Durlak et al, 2010;Gordon & Cui, 2014;Jeynes, 2007Lam & Ducreux, 2013), as well as school climate, structure, and curriculum Carpenter, Ramirez, & Severn, 2006;Hopson & Lee, 2011;Mickelson & Greene, 2006;Wentzel, 1998;Wiggan, 2007.…”
Section: Existing Gap In the Literaturementioning
confidence: 99%